Public subsidies, technology targeting and private investment: Evidence from laser land leveling in Uttar Pradesh, India - Lybbert, Travis J.; Magnan, Nicholas; Spielman, David J.; Bhargava, Anil K.; Gulati, Kajal; International Maize and Wheat Improvement Center; International Food Policy Research Institute; International Livestock Research Institute; International Rice Research Institute; WorldFish (International Food Policy Research Institute, 2014)
For many agricultural technologies, governments have the opportunity to make use of public subsidies strategically – to popularize their use among farmers, to encourage private sector participation and to improve both individual welfare and the common good. While governments may often prefer broad, unspecific subsidies to promote the rapid dissemination of these technologies, there are often better ways to use scarce public funds. This study demonstrates how better information on farmers’ willingness to pay for a technology and the private sector’s costs of technology provision can be used to design more effective uses of public subsidies.